Manajemen Tenaga Pendidik dalam Sekolah Inklusi: Systematic Literatur Review 2015-2025 - Selvia Wulandari; Nurhatatti Fuad; Sugiarto Sugiarto (Universitas Negeri Makassar, 2026)
This study investigates teacher workforce management in the implementation of inclusive education through a systematic literature review (SLR). Adhering to PRISMA 2020, searches were conducted in Scopus, Google Scholar, Garuda, and SINTA for articles published between 2015 and 2025. Of 120 records identified, 30 articles met the eligibility criteria and were thematically analyzed using the POAC framework (planning, organizing, actuating, controlling). The findings indicate that actuating is the most prominent dimension—particularly teacher training, differentiated instruction, and sustained professional development. Planning and organizing also appear frequently, including needs planning for special education support teachers (GPK), delineation of roles, and collaboration among stakeholders. In contrast, controlling remains comparatively weak and largely administrative. Overall, the management cycle appears incomplete: implementation has progressed, but continuous evaluation remains limited. These results suggest that schools and policymakers should strengthen management holistically to ensure more effective and sustainable implementation of inclusive education.